2020
DOI: 10.25165/j.ijabe.20201302.5228
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a zero-inertia model for irrigation with rapidly varied inflow discharges

Abstract: The zero-inertia model is widely used for simulating surface flow in irrigation systems. This model is accurate when inflow discharge is constant. However, simulation of irrigation systems with rapidly varied inflow discharge is needed due to the development of real time control irrigation technology. Hence, the objective of this study is to validate the zero-inertia model with rapidly varied inflow discharge. For this purpose, twenty-three border irrigation tests at a range of inflow changes on different fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…This is caused by the longer recession phase in comparison to the advance phase, causing the calibration process to focus on improving the recession phase rather than the advance phase. According to Liu et al (2020), sensitivity analysis showed that the recession phase was more sensitive to the variations in bed slope compared to the advance phase. North (2008) reported that the advance phase and recession phase were more affected by inflow discharge and slope, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…This is caused by the longer recession phase in comparison to the advance phase, causing the calibration process to focus on improving the recession phase rather than the advance phase. According to Liu et al (2020), sensitivity analysis showed that the recession phase was more sensitive to the variations in bed slope compared to the advance phase. North (2008) reported that the advance phase and recession phase were more affected by inflow discharge and slope, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…These equations can be solved by a numerical approach more easily than complete hydrodynamic equations because of their simple mathematical properties (Strelkoff et al, 2003;Zhang et al, 2017). In this context, Liu et al (2020) validated a zero-inertia model even in presence of rapidly varied inflow discharge. Naghedifar et al (2019) proposed a basin/border irrigation model combining the 2D overland flow equations, based on the diffusion-wave approximation of the SWEs, with the 3D infiltration computed by the mixed form of Richards' equation using a non-orthogonal curvilinear coordinate system to speed-up the model computation performance.…”
Section: Introductionmentioning
confidence: 94%
“…The infiltration-coefficient variability has the greatest impact on the surface water flow process and irrigation performance [29,30] so it is the only considered for convenience in the first inflow adjustment. The range of the spatial variation coefficient of the infiltration coefficient is 10-30% [27,31].…”
Section: Inflow Adjustment Simulation and Border Parametersmentioning
confidence: 99%